What we do not know about advergames: a literature review - Cañete Sanz, Laura; De La Hera, Teresa (Frontiers in Communication, 2023)
Introduction This study presents the findings of a systematic literature review on the academic study of advergames. The evolution of the marketing paradigm has recently opened new avenues for the study of advergames, such as understanding how the brand narrative could be used within a game to achieve diverse marketing objectives, their value for brand engagement through games, or new applications of the specific characteristics of emerging platforms for advergaming. Therefore, this study aims to provide an overview of the state of the art in the academic study of advergames to identify necessary expansions of academic attention to advergames to encompass the full capabilities of branded entertainment and advergame design. Methods We conducted a systematic literature review of 122 studies on the topic of advergames published between 2005 and 2021, indexed in the Web of Science Core Collection. Results The results show that academic studies on advergames primarily focused on two key research areas: (1) investigating the impact of advergames on children's health through the promotion of food products (2) and examining the effects of advergames on purchase intention. However, there was a lack of emphasis on two other important themes: (3) brand narratives and innovative forms and (4) the effects on brand loyalty. Discussion The results of this study highlight the need for a more flexible analytical approach that considers the evolving marketing ecosystem and provides theoretical insights to explore the effectiveness of advergames from a different perspective while identifying gaps in the existing literature.